Uncovering the Important Genetic Factors for Growth during Cefotaxime-Gentamicin Combination Treatment in blaCTX-M-1 Encoding Escherichia coli - Mosaed Saleh A. Alobaidallah; Vanesa García; Richard De Mets; Sandra M. Wellner; Line E. Thomsen; Ana Herrero-Fresno; John Elmerdahl Olsen (MDPI AG, 2023)
Due to the rapid spread of CTX-M type ESBLs, the rate of resistance to third-generation cephalosporin has increased among Gram-negative bacteria, especially in Escherichia coli, and there is a need to find ways to re-sensitize ESBL E. coli to cephalosporin treatment. A previous study showed that genes involved in protein synthesis were significantly up-regulated in the presence of subinhibitory concentration of cefotaxime (CTX) in a CTX-M-1-producing E. coli. In this study, the interaction between CTX and gentamicin (GEN), targeting protein synthesis, was evaluated in MG1655/pTF2, and the MIC of CTX was strongly reduced (128-fold) in the presence of this combnation therapy. Since the underlying mechanism behind this synergy is not known, we constructed a saturated transposon mutant library in MG1655/pTF2::blaCTX-M-1 containing 315,925 unique transposon insertions to measure mutant depletion upon exposure to CTX, GEN, and combination treatment of CTX and GEN by Transposon Directed Insertion-site Sequencing (TraDIS). We identified 57 genes that were depleted (log2FC ≤ −2 and with q.value ≤ 0.01) during exposure to CTX, 18 for GEN, and 31 for combination treatment of CTX and GEN. For validation, we deleted eight genes that were either uniquely identified in combination treatment, overlapped with monotherapy of GEN, or were shared between combination treatment and monotherapy with CTX and GEN. Of these genes, we found that the inactivation of dnaK, mnmA, rsgA, and ybeD increased the efficacy of both CTX and GEN treatment, the inactivation of cpxR and yafN increased the efficacy of only CTX, and the inactivation of mnmA, rsgA, and ybeD resulted in increased synergy between CTX and GEN. Thus, the study points to putative targets for helper drugs that can restore susceptibility to these important drugs, and it indicates that genes involved in protein synthesis are essential for the synergy between these two drugs. In summary, the study identified mutants that sensitize ESBL-producing E. coli to CTX and a combination of CTX and GEN, and it increased our understanding of the mechanism behind synergy between β-lactam and aminoglycoside drugs. This forms a framework for developing new strategies to combat infections caused by resistant bacteria.